Rethinking Orientalism: Women, Travel, and the Ottoman Harem by Reina Lewis (New Brunswick, NJ: Rutgers University Press, 2004. 297 pages.) (American Journal of Islam and Society, 2006)
In her book, Reina Lewis discusses how to acquire an accurate understandingof the various strands of neo-Orientalism that perpetuate long-lastingand contemporary stereotypes of Muslim women from traditional Islamicsocieties. Within the context of the current global and geopolitical landscapeas well as the alleged American war on terror, the competing western imperialistand orientalist images, along with negative stereotypes, that characterizeMuslim women are rhetorical. According to Lewis, all of these elementsare at the center of knowledge that is produced and reproduced. This bookfocuses on Ottoman women’s writing from the beginning of the twentiethcentury and traces their “travel accounts, memories, and fractions that reveala gendered counter-discourse that challenges Occidental stereotypes” (p. 1).The author’s main theme is how these writings not only challenged westernOrientalist discourses, but also intervened in the Ottoman debate aboutwomen and national emancipation. The book, which follows an interdisciplinaryapproach, is divided into six chapters.In her introduction, Lewis argues that postcolonial studies have been tooparadigmatic and narrow to include Middle Eastern and particularly Turkishexperiences, since most postcolonial theories focus on the South Asian experience.Her novel endeavor helps bridge this void in postcolonial studies.Also, she introduces “to postcolonial studies the specificities of the lateOttoman situation and bringing to the reading of Ottoman sources the criticalperspectives of postcolonial and gender theory” (p. 5). Moreover, shebrings to light some western women’s writings, such as those of GraceEllison and Lady Mary Wortley, who traveled to the East exploring the statusof Middle Eastern women and, through their writings, tried to “challengeWestern misapprehensions” of their status (p. 45) ...